XPS and ESR study of tantalum nanoparticles - Shpak, A.P.; Korduban, A.M.; Trachevsky, V.V. (Functional Materials, 2004)
The electron structure of the films formed by ensemble of tantalum nanoparticles has been studied using XPS and EPR methods. Spectra of internal atomic levels of the film surface have been obtained using step-by-step annealing in vacuum. Using Ta4f spectra decomposition into components, the kinetics of phase formation processes has been investigated. Методами РФС и ЭПР исследована электронная структура пленок, сформированных из ансамбля наночастиц тантала. Получены спектры внутренних уровней атомов поверхности пленок при ступенчатом отжиге в вакууме. По результатам разложения Та4/-спектров на компоненты изучена кинетика процессов фазообразования. Методами РФС та ЕПР досліджєно електронну будову плівок, сформованих з ансамблю наночастинок танталу. Отримано спектри внутрішніх рівнів атомів поверхні плівок при відпалі у вакуумі. За результатами розкладання Ta4f-спектрiв на компоненти вивчено кинетіку процесів фазоутворювання.